Technical influence on knowledge grid model to promote knowledge sharing in big data community - Hosseinioun, Sara; Abdullah, Rusli (Inderscience Publishers, 2022)
The significant role of big data in improving decision making, services and, productivity in organisations is not doubtable, therefore knowledge sharing is necessary to avoid redundancy and reduce time and cost. So a suitable infrastructure such as knowledge grid that can effectively capture, share, publish and manage knowledge resources to answer the questions from masses of data will be essential. This qualitative research aimed to analyse a knowledge grid model, from a technological view, in facilitating knowledge sharing among big data community. In this way, the study reviews the technology effects in the current knowledge sharing model and it also highlights the connection of knowledge grid, technology, and big data. It narrows the findings of knowledge grid components as node and link, the different layers in a knowledge grid's architecture and their condition from a technical view by analysing current knowledge grid models and their represented data. As a result, the paper clears the technological factors, their relationship, and effect in designing a knowledge grid model to promote knowledge sharing in the big data community.